Language system, translation technique, and textual tradition in the Peshitta of Kings - Dyk, Janet Wilma, 1949- (Monographs of the Peshitta Institute, 2013)
Using the VU University syntactically analyzed, hiearchically structured database of ancient languages, the authors compared the Masoretic text of Kings to the Syriac Peshitta translation. The core question in this comparison is: which deviations between the two texts are related to the requirements of the distinct language systems, which are related to other aspects of the translation process, and which are related to the transmission history of the translated text? Though linguistic and text-historical approaches differ in method and focus, research into ancient biblical translations must take both into account. On the basis of a synoptic matching at clause level, corresponding phrases within the clauses are matched, and corresponding words within phrases. A choice out of a wealth of detailed differences thus brought to light are discussed at the syntactic level at which the phenomenon best fits: word, phrase, clause and above the clause.